1984
DOI: 10.3109/00016358409041125
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline phosphatase activity and tetracycline incorporation during initial orthodontic tooth movement in rats

Abstract: The activity of alkaline phosphatase and the incorporation of tetracycline as signs of bone formation were studied after orthodontic tooth movement for 10 h to 6 days in rats. Defined low or high forces were used. A moderate activity of non-specific alkaline phosphatase was found in the periodontal membrane (PDM) in untreated rats and in rats treated with low forces. In addition, all bone surfaces were outlined with a narrow band of intense non-specific alkaline phosphatase activity that was vanadate- and leva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…In support of this finding, Lilja, Lindskog, and Hammarstrom (1984) have shown through histochemical techniques that ALP is present in the normal periodontal membrane in rats. [15] Lindhe (1996) showed that even in healthy gingiva, certain leukocytes (neutrophils) can be seen in the junctional epithelium. [16]…”
Section: Discussionmentioning
confidence: 99%
“…In support of this finding, Lilja, Lindskog, and Hammarstrom (1984) have shown through histochemical techniques that ALP is present in the normal periodontal membrane in rats. [15] Lindhe (1996) showed that even in healthy gingiva, certain leukocytes (neutrophils) can be seen in the junctional epithelium. [16]…”
Section: Discussionmentioning
confidence: 99%
“…It has a marked activity of alkaline phosphatase similar to that of the periosteum. This activity extends above the alveolar crest to the gingivai margin (Lilja et al 1984).…”
Section: Teethmentioning
confidence: 97%
“…The periodontal membrane can be regarded as a special adaptation of the periosteum (23). Enzyme histochemical studies give the impression that the periodontal membrane is a continuation of the periosteum (24). The healing of the periodontal tissues after replantation of an avulsed tooth may thus be compared with the callus formation after fracture of a bone.…”
Section: Discossionmentioning
confidence: 99%